2022
DOI: 10.1111/tpj.15955
|View full text |Cite
|
Sign up to set email alerts
|

NUCLEAR TRANSPORT FACTOR 2‐LIKE improves drought tolerance by modulating leaf water loss in alfalfa (Medicago sativa L.)

Abstract: Drought is a major environmental factor that limits the production of alfalfa (Medicago sativa). In the present study, M. sativa NUCLEAR TRANSPORT FACTOR 2-LIKE (MsNTF2L) was identified as a nucleus-, cytoplasm-, and plasma membrane-localized protein. Its transcriptional expression was highly induced by ABA and drought stress. Overexpression of MsNTF2L in Arabidopsis resulted in hypersensitivity to ABA during both the seed germination and seedling growth stages. However, transgenic Arabidopsis plants exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…Leaf epidermal permeability affected the water loss rate and plant response to drought stress. 37 The detached leaves of tobacco OE lines showed higher RWC than WT in the dark, implying that overexpression of MsKCS10 decreased nonstomatal water evaporation. The OE lines were more drought tolerant than the WT, with less wilting and higher RWC under drought stress for 10 days.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Leaf epidermal permeability affected the water loss rate and plant response to drought stress. 37 The detached leaves of tobacco OE lines showed higher RWC than WT in the dark, implying that overexpression of MsKCS10 decreased nonstomatal water evaporation. The OE lines were more drought tolerant than the WT, with less wilting and higher RWC under drought stress for 10 days.…”
Section: Discussionmentioning
confidence: 95%
“…The OE lines also showed enhanced drought tolerance with decreased oxidative damage, improved osmotic regulation capacity, and greater photosynthesis. Leaf epidermal permeability affected the water loss rate and plant response to drought stress . The detached leaves of tobacco OE lines showed higher RWC than WT in the dark, implying that overexpression of MsKCS10 decreased nonstomatal water evaporation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guaranteed incubation conditions were as follows: 16 h light/8 h dark cycle, 80% relative humidity, and 22 °C. Previous studies have indicated that H 2 O 2 , proline, malondialdehyde (MDA) and soluble sugar can be used as indicators to evaluate drought resistance in plants [ 60 ]. Our previous study found that under drought stress, the content of H 2 O 2 peaked up to 24 h and the content of malondialdehyde (MDA), proline, and soluble sugar increased continuously up to 48 h, while the soluble protein content remained basically unchanged for 24 h and then decreased significantly [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The transcriptional expression of MsNTF2L is highly induced by ABA and drought stress. The overexpression of MsNTF2L increased drought tolerance in alfalfa via the modulation of leaf water loss by regulating both stomatal density and wax deposition [ 84 ].…”
Section: Molecular Regulation Of Stomatal Density For Osmotic Stress ...mentioning
confidence: 99%